Mandated Treatment and Its Impact on Therapeutic Process and Outcome Factors - Hachtel, Henning; Vogel, Tobias; Huber, Christian G. (Frontiers in Psychiatry, 2019)
Court-mandated treatments imply a dual role for therapy providers not only of caring for, but also of having control over, involuntary clients. The impact of legal coercion on the therapeutic relationship and feelings of stigma is widely regarded as negative and detrimental for treatment outcomes. This point of view stands in contrast to advocates of the perspective that involuntary treatment can ameliorate social functioning and thus promote a better quality of life. Regarding other outcome measures, there is evidence that offender treatment is effective and leads to reduced recidivism in criminal behavior. This narrative review provides an overview of research assessing the effects of mandatory treatment on therapeutic process and outcome factors. We conclude that legal mandatory treatment does not have to necessarily result in perceived coercion and reduced satisfaction with treatment and that a caring and authoritative treatment style aids a favorable therapeutic alliance, motivation, and therapy outcomes.